2007
DOI: 10.1200/jco.2006.09.4300
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Gefitinib in Epidermal Growth Factor Receptor Fluorescence In Situ Hybridization–Positive/Phospho-Akt–Positive or Never Smoker Patients With Advanced Non–Small-Cell Lung Cancer: The ONCOBELL Trial

Abstract: Gefitinib is active and well tolerated in patients with trial characteristics, and EGFR FISH analysis is an accurate predictor for such therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
129
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(139 citation statements)
references
References 46 publications
5
129
0
5
Order By: Relevance
“…Das et al (22) showed that NSCLC cell lines harboring tyrosine kinase domain mutations exhibit marked sensitivity to irradiation, as a result of delayed DNA repair kinetics, defective radiation-induced arrest during DNA synthesis or mitosis, and pronounced increases in apoptosis or the occurrence of micronuclei. On the other hand, the ONCO-BELL study reported a poorer response rate in patients with increased EGFR copy number and p-AKT positivity, which indicate activated PI3K-AKT signaling (23).…”
Section: Discussionmentioning
confidence: 99%
“…Das et al (22) showed that NSCLC cell lines harboring tyrosine kinase domain mutations exhibit marked sensitivity to irradiation, as a result of delayed DNA repair kinetics, defective radiation-induced arrest during DNA synthesis or mitosis, and pronounced increases in apoptosis or the occurrence of micronuclei. On the other hand, the ONCO-BELL study reported a poorer response rate in patients with increased EGFR copy number and p-AKT positivity, which indicate activated PI3K-AKT signaling (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability of these markers to consistently predict clinical response is controversial (Zhu et al, 2008). Although some clinical trials have failed to find an association between response to gefitinib and expression of EGFR, several studies have shown that increased EGFR gene copy number, as determined by FISH, and EGFR protein overexpression correlated with improved response and overall survival (OS) (Hirsch et al, 2005;Cappuzzo et al, 2005aCappuzzo et al, , 2007Sequist et al, 2007). Furthermore, increased HER2 gene copy number was also found to predict response to EGFR TKIs in EGFR-positive patients with NSCLC (Cappuzzo et al, 2005a;Soh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The benefit derived from the addition of erlotinib to gemcitabine cannot be predicted based on patient characteristics as assessed by the standard processes performed in advanced and metastatic pancreatic cancer. The treatment of pancreatic cancer may be influenced by the potential of certain biomarkers to predict better response to moleculartargeted therapies (as seen in non-small cell lung cancer [NSCLC] with erlotinib and another HER-1/EGFR TKI gefitinib; also in colorectal cancer with cetuximab) [43][44][45][46][47][48][49][50][51]. The advantage of individualizing therapy to patients could be possible if we could better understand which factors predict response to treatment.…”
Section: Erlotinibmentioning
confidence: 99%